Gemini Observations of Galaxies in Rich Early Environments (GOGREEN) I: Survey description - Balogh, Michael L. (2017)
We describe a new Large Program in progress on the Gemini North and South telescopes: Gemini Observations of Galaxies in Rich Early Environments (GOGREEN). This is an imaging and deep spectroscopic survey of 21 galaxy systems at 1 < z < 1.5, selected to span a factor >10 in halo mass. The scientific objectives include measuring the role of environment in the evolution of low-mass galaxies, and measuring the dynamics and stellar contents of their host haloes. The targets are selected from the SpARCS, SPT, COSMOS, and SXDS surveys, to be the evolutionary counterparts of today's clusters and groups. The newred-sensitive Hamamatsu detectors on GMOS, coupled with the nod-and-shuffle sky subtraction, allow simultaneous wavelength coverage over λ ~ 0.6-1.05 μm, and this enables a homogeneous and statistically complete redshift survey of galaxies of all types. The spectroscopic sample targets galaxies with AB magnitudes z' < 24.25 and [3.6] μm < 22.5, and is therefore statistically complete for stellar masses M* ≳ 1010.3M⊙, for all galaxy types and over the entire redshift range. Deep, multiwavelength imaging has been acquired over larger fields for most systems, spanning u through K, in addition to deep IRAC imaging at 3.6 μm. The spectroscopy is ~50 per cent complete as of semester 17A, and we anticipate a final sample of ~500 new cluster members. Combined with existing spectroscopy on the brighter galaxies from GCLASS, SPT, and other sources, GOGREEN will be a large legacy cluster and field galaxy sample at this redshift that spectroscopically covers a wide range in stellar mass, halo mass, and clustercentric radius.